Bicomplexes and conservation laws in non-Abelian Toda models - Gueuvoghlanian, E. P. (Iop Publishing Ltd, 2001)
A bicomplex structure is associated with the Leznov-Saveliev equation of integrable models. The linear problem associated with the zero-curvature condition is derived in terms of the bicomplex linear equation. The explicit example of a non-Abelian conformal affine Toda model is discussed in detail and its conservation laws are derived from the zero-curvature representation of its equation of motion.